ANALISIS KEEFEKTIFAN VIDEO PEMBELAJARAN SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA PADA SISWA SMP DI MASA PANDEMI - Dayutiani, Gina Saadah; Fitrianna, Aflich Yusnita (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Since March 2020 the government has officially issued a circular stating that all activities that are usually carried out both inside and outside must be temporarily suspended due to the outbreak of the COVID-19 virus. The implementation of the system has an impact on educational activities that must be carried out online. Teachers and students carry out learning through thesystem online that has been provided. Through this study, researchers analyzed the effectiveness of learning videos as a medium for learning mathematics during the pandemic. The sample of this study was 60 junior high school students from private or public schools in the Mekarmukti Village area. The research instrument used was in the form of a questionnaire, then distributed vialink google form an online. The research method used is survey research method and processed using microsoft excel. Based on the results obtained from data analysis using ascale Likert, it shows that the learning video used is an effective learning media used as an online learning media for mathematics during the pandemic, seen from the interest in learning, response, and activeness of students as well as the usefulness of learning videos. in online or distance learning mathematics during a pandemic.